On Issues of Everyday Life and Social Protection of Workers in the Agricultural Sector - Eshmamatovna, Botirova Halima (European Journal of Life Safety and Stability (2660-9630), 2022)
The wide variety of ways lying under a market economy and reforms depends on the extent to which free market competition is combined with government regulation of the economy, their social orientation, and the priority given to major economic issues. The article analyzes the reforms and the results of improving the living conditions of workers in the agricultural sector in the first years of independence.